2012
DOI: 10.1021/jp302876u
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of CuI-Containing Molybdophosphate Glasses by Infrared Reflectance Spectroscopy

Abstract: Superionic glasses xCuI–(l – x)[Cu2MoO4–CuPO3] were prepared and studied by infrared reflectance spectroscopy to investigate the structure of the oxyanion matrix and the type of sites occupied by copper ions. The study was complemented by the consideration of glasses 0.67CuI–0.33[Cu2MoO4–Cu3PO4] and xCuI–(l – x)[Cu2O-nP2O5] with n = 0.33, 0.50, 1.0. The oxyanion structure of glasses xCuI–(l – x)[Cu2MoO4–CuPO3] was found to involve discrete PO4 3‑, P2O7 4‑ and MoO4 2‑ units, where P and Mo are 4-fold coordinate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…of P-O-P bridges, ν as (P-O-P), connecting pyrophosphate (Q 1 ) units, with the infrared active ν as (PO 3 2− ) mode of Q 1 units being observed at ∼1070 cm −1 . 36,39,43 The decrease of the relative intensity of both the 947 and 1070 cm −1 IR bands with increasing MnO doping is fully consistent with the corresponding Raman spectra which showed a decrease in the relative population of Q 1 units upon doping (Figs. 7 and 10).…”
Section: Ir Spectra Of Mno-doped Sp Glassessupporting
confidence: 79%
See 2 more Smart Citations
“…of P-O-P bridges, ν as (P-O-P), connecting pyrophosphate (Q 1 ) units, with the infrared active ν as (PO 3 2− ) mode of Q 1 units being observed at ∼1070 cm −1 . 36,39,43 The decrease of the relative intensity of both the 947 and 1070 cm −1 IR bands with increasing MnO doping is fully consistent with the corresponding Raman spectra which showed a decrease in the relative population of Q 1 units upon doping (Figs. 7 and 10).…”
Section: Ir Spectra Of Mno-doped Sp Glassessupporting
confidence: 79%
“…13) is consistent with this expectation, as this feature can be attributed to ν 3 (PO 4 3− ). 43 Also, the lowerfrequency feature developing at ∼565 cm −1 can be associated with the ν 4 (PO 4 3− ) mode of Q 0 species. 43 However, quantification of the effect of doping on the basis of IR spectra alone is difficult because of the strong overlapping of the different phosphate and sulfate vibrational bands.…”
Section: Ir Spectra Of Mno-doped Sp Glassesmentioning
confidence: 97%
See 1 more Smart Citation
“…3 ), units can be seen. The infrared bands between 700 and 850 cm 1 are associated with symmetric stretching modes of P-O-P linkages, while the broad band observed in the far-IR region, 200-550 cm 1 , is assigned to vibrations of Li cations against their sites in the oxide glass matrix [9,10,[35][36][37]. On the other hand, the lithium phosphate film (i.e., sample N0-10 deposited under Ar) presents large spectral variations after air exposure (Fig.…”
Section: Stability Of Deposited Films To Air Exposurementioning
confidence: 99%
“…Kamitsos et al [31] have observed for alkali oxidecontaining glasses the occurrence of more than one cation motion band in the far-IR originating from the existence of more than one type of cation-hosting anionic sites differing mainly in the coordination of alkali cation. Following this methodology, the far-IR envelope has been analyzed using spectral decomposition based on similar treatments for the far-IR spectra reported for borate, phosphate, and germanate glasses [31,35,36,44,45]. Figure 4 presents the decomposition of the far-IR region for samples N0-10, N5-5, and N10-0.…”
Section: Stability Of Deposited Films To Air Exposurementioning
confidence: 99%